Colchicine을 이용한 잡감류 감귤의 4배체 유기 - 이동훈(Dong Hoon Lee); 박재호(Jae Ho Park); 문영일(Young Eel Moon); 안현주(Hyun Joo An); 윤수현(Su Hyun Yun); 현재욱(Jae Wook Hyun); 최혜운(Hye Un Choi); 강성구(Sung Ku Kang) (Weon'ye gwahag gi'sulji, 2008)
4배체 감귤 품종육성을 위하여 ‘팔삭’(Citrus hassaku Tan.) 과 ‘신감하’(C. shinamanatsu Tan.)의 잎을 제거한 액아의 기부로 0.05, 0.1, 0.5 및 0.9% colchicine 수용액을 0.1mL주입 처리하였다. 처리한 눈에서 발생한 가지의 배수성을 조사한 결과, ‘팔삭’은 0.1% 처리구에서 1개, ‘신감하’에서 는 0.5% 처리구에서 1개의 4배성 개체가 확인되었다. 확인 된 4배체는 이듬해 탱자대목에 절접한 후 육묘한 결과, colchicine 처리 후 3년째 정상적으로 개화하였다. 개화한 개체의 배수성과 잎의 기공 및 생식기관의 특성을 조사한 결과, 정단분열조직의 염색체수는 2n=4X=36인 것으로 확 인되었으며 2배체에 비하여 잎의 기공, 약 및 화분의 크기가 증가하였다. To induce tetraploids of miscellaneous citrus, ‘Hassakku’ (Citrus hassaku Tan.) and ‘Shinamanatsu’ (C. shinamanatsu Tan.), 0.1 mL of 0.05, 0.1, 0.5 and 0.9% colchicine solutions was injected into leaf detached axillary buds. As a result of ploidy analysis, newly developed young leaves of the treated buds revealed one tetraploid shoot of ‘Hassaku’ and ‘Shinamanatsu’ in the 0.1% and 0.5% colchicine-treated buds, respectively. The putative tetraploid shoots were successfully top-grafted onto trifoliate orange. In third year from colchicine treatment, they flowered, and produced larger leaf stomata, anthers and pollen grains than their original diploids. The chromosome number of their shoot tip merismatic tissues was 2n=4X=36. KCI Citation Count: 0